Parvovirus Infection and Seropositivity in a Group of Pregnant Women - Coşkun, Ayhan; Kıran, Gürkan; Güven, Alanur Menekşe; Özdemir, Özgür; Köstü, Bülent; Aral, Murat (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: Detection of parvovirus B19 seropositivity in a group of pregnant women. STUDY DESIGN: Parvovirus B19 IgM and IgG seropositivity was investigated in 58 pregnant women. RESULTS: None of the 58 pregnant women had parvovirus B19 IgM seropositivity and 27% (n: 16) of the patients had IgG seropositivity. CONLUSIONS: Parvovirus B19 IgG seropositivity increases in pregnants by aging and it is reported as 60- 70 %. In our study the seropositivity was lower than the rates reported in the literature. Parvovirus B 19 infection is rare during pregnancy. Maternal- to- foetal transmission during acute maternal infection is about 33 %. Most of the foetal infections are asymptomatic. Common clinic presentations are miscarriage or foetal non-immun hydrops. In our opinion, routine screening of parvovirus B 19 infection should not recommended during pregnancy and screening should be limited with the hydropic fetuses because of some reasons including rarity of acute maternal infection during pregnancy, difficulty in predicting of foetal transmission, and irrelevance with fetal anomalies, rarity of miscarriage and hydrops foetalis even if fetal infection is considered.